PP.30.28: EFFECT OF EXERCISE TRAINING ON THE RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM IN HEALTHY INDIVIDUALS. (June 2015) - Goessler, K.; Polito, M.; Cornelissen, V.
Abstract : Objective: The aim of this systematic review and meta-analysis was to evaluate the effect of exercise training on parameters of the renin angiotensin aldosterone system (RAAS) in healthy adults and to investigate the relation with training induced changes in blood pressure. Design and method: A systematic search was conducted and we included randomized controlled trials lasting 4 weeks or more investigating the effects of exercise on parameters of the RAAS in healthy adults (age 18 years or more) and published in a peer-reviewed journal up to December 2013. Fixed effects models were used and data are reported as weighted means and 95% confidence limits (CL). Eleven randomized controlled trials with a total of 375 individuals were included. Results: Plasma renin activity was reduced after exercise training {n = 7 trials, standardized mean difference-0.25 (95%CL -0.5 to -0.001), p = 0.049} whereas no effect was observed on serum aldosterone {(n = 3 trials; standardized mean difference-0.79 (-1.97 to +0.39)} or angiotensin II {n = 3 trials; standardized mean difference -0.16 (-0.61 to +0.30)}. Significant reduction in systolic blood pressure -5.65 mmHg (-8.12 to -3.17) and diastolic blood pressure -3.64 mmHg (-5.4 to -1.91) following exercise training were observed. No relation was found between net changes in plasma renin activity (PRA) and net changes in blood pressure (P > 0.05) Conclusions: To conclude, although we observed a significant reduction in plasma renin activity following exercise training this was not related to the observed BP reduction. Given the small number of studies and small sample sizes, larger well-controlled randomized studies are required to confirm our results and to investigate the potential role of the RAAS in the observed improvements in blood pressure following exercise training.